Incidence of Childhood Acute Rheumatic Fever in Malatya Region (Annals of Medical Research, 2021)
Aim: Acute rheumatic fever is a multisystemic disease related to an immun reaction against group A beta hemolytic streptococcus infection, may recur and the social and economic status of the host affects its morbidity and mortality.Acute rheumatic fever is the most common cause of acquired heart disease in children and young adults in the developing countries.There are only a few limited studies in Turkey for incidence of rheumatic fever.
Keywords: Rheumatic Fever; Carditis; Malatya.